A new species of Galium (Rubiaceae) from Southwest Anatolia, Turkey - Daşkin Ruzi̇ye; Bağçivan, Gülşah (Phytotaxa, 2017)
Galium cariense, a new species from serpentine scree in Denizli and Muğla provinces, SW Anatolia, Turkey, is here described and illustrated. The new species belongs to Galium section Kolgyda and is similar to G. bracteatum, G. penduliflorum and G. peplidifolium, from which it differs by its short, glabrous, reddish stems, small, ovate-oblong, equal cauline leaves, thyrsoid inflorescences, acute to obtuse corolla lobes and narrowly oblong, papillate mericarps. The diagnostic characters of G. cariense and related species are discussed. Moreover, ecology, conservation status and the geographical distribution of the new species are presented and its mericarp surface characteristics are investigated using scanning electron microscopy.